2021
DOI: 10.1364/prj.440935
|View full text |Cite
|
Sign up to set email alerts
|

Slide-free histological imaging by microscopy with ultraviolet surface excitation using speckle illumination

Abstract: Microscopy with ultraviolet surface excitation (MUSE) is a promising slide-free imaging technique to improve the time-consuming histopathology workflow. However, since the penetration depth of the excitation light is tissue dependent, the image contrast could be significantly degraded when the depth of field of the imaging system is shallower than the penetration depth. High-resolution cellular imaging normally comes with a shallow depth of field, which also restricts the tolerance of surface roughness in biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The results of searching for a match with a sample of the 108 th person are as shown in Fig. (9). As is visible, the maximum response is obtained at the 108 th sample i.e.…”
Section: Outputmentioning
confidence: 89%
See 2 more Smart Citations
“…The results of searching for a match with a sample of the 108 th person are as shown in Fig. (9). As is visible, the maximum response is obtained at the 108 th sample i.e.…”
Section: Outputmentioning
confidence: 89%
“…Nguyen [8] examined a number of pre-trained CNN models, such as DenseNet, AlexNet, VGGNet, InceptionNet, and ResNet, in order to extract readily available CNN characteristics for precise iris identification and retina recognition. He Wong et al [9] suggested using ResNet, or the deep residual network, to recognize images. Training the smaller iris datasets can benefit greatly from this architecture's ability to reduce overfitting and improve accuracy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DUV-excited fluorescence microscopy, also known as MUSE, has been celebrated for its simplicity and effectiveness in concept -the combination of oblique DUV illumination and widefield detection. However, prior published illustrations of real-world implementations [14,15,35,[56][57][58] showed inevitably large and complex setups, with the notable exception of Pocket MUSE, which is generally incompatible with large surgical or mesoscale samples [16]. Also notable in the MUSE literature was the conspicuous omission of imaging capabilities at >40X magnification, a mainstay of biomedical inspection and unusually difficult in MUSE due to the classically awkward implementation of oblique illumination.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, deep learning techniques have been widely used in several research fields, such as photonics research [ 9 , 10 , 11 ], biological imaging [ 12 , 13 ], material science [ 14 ], and image super-resolution [ 15 , 16 ], all of which demonstrate the advantages of these techniques. Similarly, the strategy based on deep learning has achieved excellent performance in a series of biometric technology problems, such as emotion recognition [ 17 , 18 ], gait recognition [ 19 ], fingerprint recognition [ 20 ], and voice signal recognition [ 21 ].…”
Section: Introductionmentioning
confidence: 99%